2020
DOI: 10.3390/cells9040939
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Tracking of Hematopoietic Stem Cells in a Bone Marrow Transplant Model

Abstract: The hematopoietic stem cell engraftment depends on adequate cell numbers, their homing, and the subsequent short and long-term engraftment of these cells in the niche. We performed a systematic review of the methods employed to track hematopoietic reconstitution using molecular imaging. We searched articles indexed, published prior to January 2020, in PubMed, Cochrane, and Scopus with the following keyword sequences: (Hematopoietic Stem Cell OR Hematopoietic Progenitor Cell) AND (Tracking OR Homing) AND (Trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 77 publications
(494 reference statements)
0
25
0
Order By: Relevance
“…The quantification of iron load internalized into BM-MNC by NIRF, MRI, and ICP-MS (Table 2) showed signal detection according to the signal detection limitation of each technique as a function of their sensibility, spatial, and temporal resolutions [17,46]. Some studies reported an internalization of 0.69 ± 0.08 [47]; 1.33 ± 0.2 [48]; 2.01 ± 0.10 pg [49] of nanoparticles per HSC.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The quantification of iron load internalized into BM-MNC by NIRF, MRI, and ICP-MS (Table 2) showed signal detection according to the signal detection limitation of each technique as a function of their sensibility, spatial, and temporal resolutions [17,46]. Some studies reported an internalization of 0.69 ± 0.08 [47]; 1.33 ± 0.2 [48]; 2.01 ± 0.10 pg [49] of nanoparticles per HSC.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, studies about cells homing/tracking after BTM have used ex vivo techniques to quantify HSC in recipient animal; this type of analysis cannot generate data on the migration or grafting dynamic in a single animal longitudinally, since it requires euthanasia at the point of analysis [14][15][16]. However, the cell homing and grafting data can be obtained in a non-invasive way with the use of the molecular image technique [17]. The molecular image comprise a group of image techniques that use the target molecules to track biological processes via in vivo analysis, in a non-invasive way, besides allowing the quantitative analysis [18].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations